Line and Scribble - Vogrig, Debora; Valentinis, Pia (San Francisco : Chronicle Books, 2021)
Line goes straight on her way, while Scribble wanders and zigzags, but they are still best friends and can work together with their individual perspectives to make art.
new kids book 2022 spring.
Ages 3-5.
Grades K-1.
Keywords: Drawing -- Juvenile fiction; Perspective -- Juvenile fiction; Best friends -- Juvenile fiction; Drawing -- Fiction; Perspective (Philosophy) -- Fiction; Difference (Psychology) -- Fiction; Friendship -- Fiction